MEREFLEKSIKAN SIKAP DAN TANGGUNG JAWAB KEPEMIMPINAN SEBAGAI TELADANAN KEPEMIMPINAN KRISTEN MENURUT YOHANES 10:1-21 - Pitriani Padatu; Leonardo Paundanan, Firmansyah Ratte, Delfo, Barsitha Tanga (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research aims to delve into and analyze Jesus' teachings on leadership in the Gospel of John 10:1-21, with a focus on attitude and responsibility as exemplars of Christian leadership. The research methodology employed includes exegetical analysis to understand the historical and theological context of this passage, as well as interpretive analysis and literature review to gain a deeper understanding. The findings of the research indicate that John 10:1-21 highlights crucial aspects of Christian leadership, including a profound understanding of the flock, self- sacrifice, and openness to the voice and will of God. Jesus, as the Good Shepherd, sets an example of leadership that prioritizes service, protection, and guidance with love. Furthermore, this research also identifies practical implications of these teachings for Christian leaders in the modern context. By applying the principles revealed in John 10:1-21, Christian leaders can serve as role models, inspiring and guiding their flock towards spiritual growth and steadfast fellowship in faith. In conclusion, this research makes a significant contribution to the understanding of Christian leadership based on the teachings of Jesus in John 10:1-21. The findings of this research can serve as a foundation for developing and strengthening Christian leadership in the present-day church and society, with the aim of glorifying God and serving others with love and fidelity.